1984
DOI: 10.1038/hdy.1984.93
|View full text |Cite
|
Sign up to set email alerts
|

Dosage compensation of the sex-linked enzyme phosphoglucomutase in the orthoptera

Abstract: SUMMARYSex-linkage of phosphoglucomutase (PGM) is widespread in the Orthoptera. For each of three species studied (representing the two suborders), the specific activity of PGM in males (the heterogametic sex) is almost identical to that in females, providing direct evidence that the difference in gene dose of a sex-linked locus in males and females is compensated in the Orthoptera. The Orthoptera is only the third group for which compensation has been demonstrated. Dosage compensation has been investigated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…), where females have two X chromosomes and males one. Various orthopteran species have been shown to have sex-linkage at a Pgm locus (Hebbert 1984). Conservation of this X chromosome trait in Stenopelmatidae would explain the hemizygous nature of the male hybrid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), where females have two X chromosomes and males one. Various orthopteran species have been shown to have sex-linkage at a Pgm locus (Hebbert 1984). Conservation of this X chromosome trait in Stenopelmatidae would explain the hemizygous nature of the male hybrid.…”
Section: Discussionmentioning
confidence: 99%
“…If hybrids do exist, then the direction of the cross can be established by use of sex-linked alleles. Eleven species of Orthoptera (representing both suborders Caelifera and Ensifera) have sex linkage of a phosphoglucomutase (Pgm) locus (Hebbert 1984). We used a stain to examine phosphoglucomutase in these weta.…”
Section: Introductionmentioning
confidence: 99%
“…Because PGM is a monomer, homozygous individuals can be recognized by a single band, whereas heterozygous individuals have a doublebanded phenotype. An initial screening of adults revealed that PGM is sex-linked in G. sigillatus, as it is in other Orthoptera (Hebbert 1984); males, because they are XO, exhibit only a single fast or slow band, whereas females (XX) can exhibit either one or two bands. Hence, only the paternity of female offspring could be resolved on the basis of this allozyme.…”
Section: Electrophoretic Determination Of Paternitymentioning
confidence: 99%
“…(Hebbert 1984). All individuals are homozygous for the common allozyme unless specified in the variants column.…”
Section: Methodsmentioning
confidence: 99%